Association of total serum antioxidant capacity with the Tei index in echocardiography in patients with microvascular angina. Issue 7 (November 2015) - Kilic, Alparslan; Yarlioglues, Mikail; Ercan, Ebru Akgul; Duran, Mustafa; Ugurlu, Murat; Oksuz, Fatih; Ozdemir, Sedat; Kurtul, Alparslan; Karadeniz, Muhammed; Murat, Sani Namik; Korkmaz, Sule; Demirtas, Selda
<x xml:space="preserve">Abstract</x> Objectives Cardiac syndrome X (CSX) is a condition characterized by exercise-induced chest pain that occurs considering a normal coronary angiogram. We aimed to investigate the total serum antioxidant capacity (TAC) and biventricular global functions using echocardiography in patients with CSX. Patients and methods The study population included 55 patients with typical anginal symptoms and a positive exercise stress test, or ischemia in myocardial perfusion scintigraphy and normal coronary arteries detected angiographically, and 49 healthy volunteers with atypical chest pain and a negative stress test. TAC was assessed from blood samples. Transthoracic echocardiography was performed for the entire study population. The Tei index was calculated using the formula IVCT+IVRT/ET. Results TAC was found to be significantly lower in the CSX group compared with the control group (0.70±0.37 vs. 1.5±0.30, respectively, P<0.001). The Tei index was significantly higher in patients with CSX than the control group (0.60±0.18 vs. 0.42±0.12, respectively, P<0.001).There was a significant and inverse relationship between TAC and the Tei index (r=−0.41, P<0.001). When we divided the study population according to the normal range of TAC into the decreased TAC group (<1.30 mmol/l), the normal TAC group (1.30–1.77 mmol/l), and the increased TAC group (>1.77 mmol/l), it was found that the Tei index was higher in the decreased TAC group compared with the other groups (0.66±0.18 vs. 0.49±0.10 and 0.46±0.13 mmol/l, P<0.001, respectively). Conclusion Our study suggested that TAC was significantly decreased in CSX patients and decreased antioxidant levels were related to impaired Tei index in echocardiography in patients with microvascular angina.